PENGEMBANGAN PENDIDIKAN BERBUDAYA NIRKEKERASAN DI MADRASAH IBTIDAIYAH SE-KABUPATEN JEMBER - Nino Indrianto; Zainuddin Al-Haj Zaini; Nina Hayuningtyas (STAI Ma'had Aly Al-Hikam Malang, 2019)
The number of violence in the education environment is still a problem for education in Indonesia. Madrasah as part of the national education system must be able to provide solutions to these problems. The development of non-violent culture education is expected to be able to provide solutions, so that produces some graduates who have self-control, noble character and have a sense of togetherness as one nation and country. This research aimed to determine prevention and control efforts and also the sanctions against perpetrators of violence in realizing a non-violence culture at MIN 1 and MIN 6 Jember. This type of research was qualitative research with sampling techniques using purposive sampling. Furthemore, the methods used to collect data were Â documentation, interviews, and observation. The results of this research indicated that: 1) MIN 1 Jember undertook preventive measures by making activities that can build communication among the members of madrasah, while MIN 6 Jember took preventive action efforts by making activities that can build closeness among the members of madrasah, 2) MIN 1 and MIN 6 Jember ,in efforts to deal with violence, followed up the violence cases propotionally, 3) MIN 1 and MIN 6 Jember gave the sanctions or punishments to the perpetrators of violence verbally, writtenly, and other educational sanctions.